A Behavioral Approach Design for Supporting Sitting Facilities at The Lounge Area Of Minangkabau International Airport (BIM) - Alghifary, Faiz; Hanom, Imtihan (Institut Seni Indonesia Denpasar, 2024)
Minangkabau International Airport (BIM) located in West Sumatera is used as the main air transportation mode to travel outside the province. When waiting for flights, passengers will be in the airport lounge. However, the airport lounge still doesn’t have supporting facilities to maximize activities while in the lounge area. This research uses descriptive qualitative methods with direct observation, distributing questionnaires, and literature study as a sources. An environment can be said to be good if it can meet the needs of humans in it. Therefore, a supporting facility was created to maximize passengers' activities while in the airport lounge. This supporting facility also has a high level of mobility so that it can meet the needs of airport passengers who have high mobility in the form of a multifunctional partition. In addition, this facility uses cultural elements in the form of one typical Minangkabau motif, namely